Vous êtes sur la page 1sur 7

1 4

¯

C( C) +()

P (− | C) = 1

4

P (C | −) =

1

¯

4 P( C | +) =

2

3

P (+ |

C) = 2 3

¯

P (− | C) = P (C)

1 4

= 4 1

P(C)

P (+ |

P (− | C) =

1

4

P (+ |

¯

C) =

3 2

¯

C)

=

¯

P (+∩ C) 2 = P (+) 3
P (+∩ C)
2
=
P (+)
3

P (+ | C) = 1 P (− | C) = 1 1 4 = 3

4

| C ) = 1 − P ( − | C ) = 1 − 1

P (C) = 0.01 2 × 2

¯

Y = (+, ) X = (C, C)

2 × 2

+

C

0.0075

0.0025

0.01

¯

C

0.66

0.33

0.99

0.6675

0.3325

1

¯

P (C) = 0.01 P ( C) = 1 P (C) = 0.99

P (− | C)

4 1 × 0.01 = 0.0025. P (+ C) =

P (− ∩ C) = P (− | C) · P (C) =

0.01 0.0025 = 0.0075

P (− |

¯

P (− |

1 3 × 0.99 = 0.33

¯

C) ¯ = 1 P (+ | C) = 1 2

¯

¯

¯

3

=

¯

1

3

C)·P( C) =

P (+ C) = 0.99 0.33 = 0.66 P (+) = 0.0075 + 0.66 = 0.6675

C) P (−∩ C) = P(− |

P () = 0.0025 + 0.33 = 0.3325

P ( − ) = 0 . 0025 + 0 . 33 = 0 . 3325

P (+) = 0.6675 P () = 0.3325

P (+) = 0 . 6675 P ( − ) = 0 . 3325

P (C | +)

P (C | +) = P (C+)

0.01124

0.0075

0.6675

P (+)

=

= 0.01124

P ( − ) = 0 . 3325 P ( C | +) P ( C

X = (1 = 2 = ) Y

(1 = 2 = ) π i = P(Y

= 1 | X = i) i = 1, 2

= π 1 = 1 π 2

=

P (Y = 1 | X = 1) π 1

P (Y = 2 | X = 2)

1 π 2

π 1 P ( Y = 2 | X = 2) 1 − π 2 γ

γ π 1 γ

π 1 γ + π 2 (1 γ)

P (A | B) = P(B | A) · P(A)

P (Y = 1)

P(B)

P (Y

= 1) = P (Y

=

1 X = 1) + P (Y

= 1 X = 2)

 

= P (Y

= 1 | X = 1) · P (X = 1) + P (Y

= 1 | X

=

2) · P (X = 2).

P (X = 1 | Y = 1)

P (X = 1 | Y

= 1) = P (Y

= 1 | X = 1) · P (X = 1)

P (Y = 1)

=

=

P (Y

= 1 | X = 1) · P (X = 1)

P (Y

= 1 | X = 1) · P (X = 1) + P (Y

π 1 γ

π 1 γ + π 2 (1 γ) .

= 1 | X = 2) · P (X = 2)

π 2 (1 − γ ) . = 1 | X = 2) · P (

γ = 0.01 = 0.86 = 0.88

= 1 π 2 = 0.88 π 2 = 1 0.88 = 0.12

π 1 γ

π 1 γ + π 2 (1 γ) =

0.86 × 0.01 0.86 × 0.01 + 0.12(1 0.01) = 0.0675.

π 1 γ

π 1 γ + π 2 (1 γ)

7 5 . π 1 γ π 1 γ + π 2 (1 − γ )

2 × 2 X Y

2 × 2

 

 

Y

= 1

Y

= 2

X

= 1

0.0086

0.0014

0.01

X

= 2

0.1188

0.8712

0.99

0.1274

0.8726

1

P (Y

P (Y = 2 X = 1) = 0.01 0.0086 = 0.0014

= 1 X = 1) = P (Y

= 1 | X = 1) · P (X

= 1) = 0.86 × 0.01 = 0.0086

 

P (X

= 2) = 1 0.01 = 0.99

 

P (Y =

1 X

= 2) = P (Y

= 1 | X = 2) · P (X

= 2) = 0.12 × 0.99 = 0.1188

P (Y = 2 X = 2) = 0.99 0.1188 = 0.8712.

( Y = 2 ∩ X = 2) = 0 . 99 − 0 . 1188

1.3

62.4

ˆ

∆ = p 1 p 2

= 62.4 1.3

= 61.1 .

π π 2 p 2 = 48

1

1

p

3 = 61 . 1 . π π 2 p 2 = 48 1 1 p

0

= 61 . 1 . π π 2 p 2 = 48 1 1 p 0

11

10

10

3

+1

3

10

3

10

+ 1 = 0.2308

11

10 + 1 = 0.5238 11 10
10
+ 1 = 0.5238
11
10

1.7 1.7

1.7

1 1 p 0 1 1 1 0 1 0 3 + 1 3 10 3

45%

π π 2 = 10.45 = 0.55

1

π 2

π 1

=

1

0.55 = 1.8182

0 . 45 = 0 . 55 1 π 2 π 1 = 1 0 .

35 0.001304 0.000121

ˆ

∆ = p 1 p 2 = 0.001304 0.000121 = 0.001183

π 1

= 10.7769

π 2 =

0.001304

0.000121

. 001183 π 1 = 10 . 7769 π 2 = 0 . 001304 0 .

π

π 2 /(1π 2 ) = 0.001304/(10.001304)

1 /(1π 1 )

0.000121/(10.000121) = 10.7896

1 35 35 π 1 π 2 1 π 1 1 π 2

1 π 2 1 − π 1 1 − π 2 11 . 4 11 .

11.4

11.4

11.4

1 − π 1 1 − π 2 11 . 4 11 . 4 11 .

2.9

θ =

M = 0.2544 π M =

F

M

θ = 11.4 F

F

F

+1

= 2.9

M = M +1 2.9 = 2.9+1 =
M
=
M
+1
2.9
=
2.9+1 =

0.2544

0.2544+1 = 0.2028 π F =

0.7436

R R

R

π F

π M

= 0.7436

0.2028 = 3.6667

= 0 . 2028 π F = 0 . 7436 R R R π F π

0.906 0.847

60% 60% 57%

θ = 57%

B

W

=

π B /(1π B ) ) π W /(1π W

=

0.847/0.153

0.906/0.094 = .5744

0 . 1 5 3 0 . 9 0 6 / 0 . 0 9 4

60%

60%

π B π W =
π B
π W =

0.847

0.906

= 0.9349 93%

11.7 s 0 < s < 20 26.1 s 20

s 20 0 < s < 20 26.1

11.7 = 2.2

2 × 2 (Y ) (X ) 0 < s < 20 odds s c = 26.1 s 20

odds ss

= 11.7 s 20

0 < s < 20 odds ss

91% 83% Y X

odds

odds c

= 26.1×odds c 11.7×odds c

odds s

= 2.2

= 26 . 1 × odds c 11 . 7 × odds c odds s =

Y X X Y

X Y

11 . 7 × odds c odds s = 2 . 2 Y X X Y

X Y

2 × 2 b w

Y

X

b

w

b

0.91

0.09

w

0.17

0.83

X Y π

π 2 /(1 π 2 ) = 0.91/0.09

1 /(1 π 1 )

0.17/0.83 = 49.37

49.37

π 2 / (1 − π 2 ) = 0 . 91 / 0 . 09

= w | X = w) = P(X = w | Y

= w) · P(Y

= w)

P (Y

P(X = w) P (Y = w ) P (X = w )

w

P ( X = w ) P ( Y = w ) P ( X =

198 19, 934 193 19, 942

2×2

2 × 2

198 193 19 , 736 19 , 749 19 , 934 19 , 942

198 193 19 , 736 19 , 749 19 , 934 19 , 942

198

193

198 193 19 , 736 19 , 749 19 , 934 19 , 942

19, 736

19, 749

19, 934

19, 942

19 , 736 19 , 749 19 , 934 19 , 942 ˆ θ = n

ˆ

θ

= n 11 /n 12

n 21 /n 22

= 198/19,736

193/19,749 = 1.0266 1

, 736 1 9 3 / 1 9 , 7 4 9 = 1 . 0266

95%

log

95%

ˆ

θ±Z α/2 ·σ log

ˆ

θ

σ log

ˆ

θ

=

1

n

11

+

1

n

12

+

1

n

21

+

1

n 22

ˆ

log θ = log 1.0266 = 0.0114

ˆ

σ log θ

=

1

198 +

1

19736 +

1

193 +

1

19749 = 0.1017.

ˆ

log

θ ± Z α/2 · σ log

θ ˆ 0.0114 ± 1.96 × 0.1017 = (0.18793, 0.21073) 95%

(e 0.18793 ,

e 0.21073 ) = (0.82867, 1.23458)

ˆ

θ = 1

. 2 1 0 7 3 ) = (0 . 82867 , 1 . 23458) ˆ

509

116

625

398

104

502

907

220

1127

90%

(p 1 p 2 )±Z α/2 p 1 (1p 1 )

p 1 = 509

n

1

+ p 2 (1p 2 )

n

2

= 0.8144 p 2 = 398

502

625

= 0.7928 90%

(0.8144 0.7928) ± 1.645 × 0.8144 × 0.1856

625

0.7928 × 0.2072

+

502

= 0.0216 ± 0.0392

= (0.01764, 0.06084).

π 1 π 2 < 0 π 1 < π 2

. π 1 − π 2 < 0 π 1 < π 2 . 90% log

.

90%

log

ˆ

θ ±Z α/2 ·σ log

θ ˆ

log

log θ = log 509/116

ˆ

398/104 = 0.05941

ˆ

σ log θ

ˆ

θ ± Z α/2 · σ log

ˆ

θ

=

1

509 +

1

1

116 + 398 +

1

104 = 0.15071

= 0.05941 ± 1.645 × 0.15071

= (0.18851, 0.30733)

90% (e 0.18851 , e 0.30733 ) = (0.82819, 1.35979)

ˆ

θ = 1

. 3 0 7 3 3 ) = (0 . 82819 , 1 . 35979) ˆ

p

π ij = π i ·π j i j

H 0 X 2 =

µˆ ij = n i ·n j

(n ij µˆ ij ) 2 µˆ ij

ij

n

= 625 × 907

µˆ

625 × 220

µˆ

502 × 907

µˆ

µˆ 22 = 502 × 220

11

12

21

1127

1127

1127

1127

=

=

=

=

=

=

502.9947

122.0053

404.0053

97.9947

X 2 = (509 502.9947) 2

502.9947

+ (116 122.0053) 2

122.0053

+ (398 404.0053) 2

404.0053

+ (104 97.9947) 2

97.9947

= 0.8246.

(I 1)(J 1) = (2 1)(2 1) = 1 p 0.3638

(104 − 97 . 9947) 2 97 . 9947 = 0 . 8246 . ( I